2021
DOI: 10.21203/rs.3.rs-488747/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Developing cardiometabolic risk classifiers for youth using handgrip strength, anthropometrics, and demographics: a machine learning approach leveraging National Health and Nutrition Examination Survey Data

Abstract: Background Handgrip strength associates with cardiometabolic (CMB) risk. Health-related physical fitness (HRPF) testing in schools do not explicitly predict CMB disease risk, and commonly engender anxiety, teasing and taunting by peers. Further, school-based screening for hyperinsulinemia using acanthosis nigricans likely misses nascent CMB risk factors like dyslipidemia. This study examined the feasibility of leveraging anthropometrics, demographics, and handgrip strength data to build optimal CMB risk classi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…Toyin Ajisafe utilized six methods of machine learning algorithm, which are coarse tree, quadratic discriminant, logistic regression, kernel naïve Bayes, quadratic SVM, and weighted KNN, to see if it was possible to use anthropometrics, demographics, and handgrip strength data to build optimal Cardiometabolic (CMB) risk classifiers [18]. The researcher found that the coarse tree outperformed the other machine learning method with an accuracy of 85% in classified CMB risk data.…”
Section: A Study On the Correlation Between Hand Grip And Age Using S...mentioning
confidence: 99%
“…Toyin Ajisafe utilized six methods of machine learning algorithm, which are coarse tree, quadratic discriminant, logistic regression, kernel naïve Bayes, quadratic SVM, and weighted KNN, to see if it was possible to use anthropometrics, demographics, and handgrip strength data to build optimal Cardiometabolic (CMB) risk classifiers [18]. The researcher found that the coarse tree outperformed the other machine learning method with an accuracy of 85% in classified CMB risk data.…”
Section: A Study On the Correlation Between Hand Grip And Age Using S...mentioning
confidence: 99%